Exploring Corporate Social Responsibility in the U.K. Asian Small Business Community - Worthington, Ian (Journal of business ethics, 2006)
Within the limited, but growing, literature on small business ethics almost no attention has been paid to the issue of social responsibility within ethnic minority businesses. Using a social capital perspective, this paper reports on an exploratory and qualitative investigation into the attitudinal and behavioural manifestations of CSR within small and medium-sized Asian owned or managed firms in the U.K., with particular reference to the distinctive factors motivating organisational responses. It offers alternative explanations of entrepreneurial behaviour and suggests areas for further research.